Ettore Sottsass architect and designer - Labaco, Ronald T; Sottsass, Ettore 1917-.; Doordan, Dennis P. (New York Merrell Pubishers in association with Los Angeles County Museum of Art, 2006)
"Ettore Sottsass: Architect and Designer - the first significant study of the work of Sottsass for over a decade - emphasizes the continuing diversity and innovation of his professional life while illuminating his personal design philosophy, his belief in the intimate relationship between design and the individual, and his fundamental humanity and joie de vivre. Drawing in particular on the work of the two decades since Sottsass left the Memphis collective, this book reassesses his relationship to Modernism and Postmodernism, analyzes the increasing importance to Sottsass of his own architectural practice, and considers both his acceptance and his rejection of the traditional use of materials. In a series of interviews specially undertaken for this book, Sottsass reflects on the cross-currents of ideas and influences that have guided his long career."
Keywords: Sottsass, Ettore -- 1917- -- Exhibitions; Sottsass associati (Milan, Italy) -- Exhibitions; Design -- Italy -- History -- 20th century -- Exhibitions